2023
DOI: 10.2147/ijn.s388349
|View full text |Cite
|
Sign up to set email alerts
|

How Advanced are Cancer Immuno-Nanotherapeutics? A Comprehensive Review of the Literature

Abstract: Cancer is a broad term for a group of diseases involving uncontrolled cell growth and proliferation. There is no cure for cancer despite recent significant improvements in screening, treatment, and prevention approaches. Among the available treatments, immunotherapy has been successful in targeting and killing cancer cells by stimulating or enhancing the body's immune system. Antibody-based immunotherapeutic agents that block immune checkpoint proteins expressed by cancer cells have shown promising results. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 128 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…In the past decade, immune cells have gained significant attention in TME research due to their capacity to regulate tumor growth ( 16 ). Despite incomplete comprehension of the role of B cells in cancer research, their heterogeneity has been demonstrated as indispensable in the TME ( 17 ).…”
Section: B Cells and The Tumor Microenvironmentmentioning
confidence: 99%
“…In the past decade, immune cells have gained significant attention in TME research due to their capacity to regulate tumor growth ( 16 ). Despite incomplete comprehension of the role of B cells in cancer research, their heterogeneity has been demonstrated as indispensable in the TME ( 17 ).…”
Section: B Cells and The Tumor Microenvironmentmentioning
confidence: 99%
“…27,29,30 However, selecting cancer antigens is challenging due to the heterogeneity of individual cancers, and many cancer antigens lack immune activation ability. 26,28,31 Consequently, various methods are being explored for cancer immunotherapy including thermal immunotherapy, which has shown promise in achieving efficient cancer therapy. 32−34 Inorganic nanoparticles have been widely used due to their ability to generate thermal effects.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, advanced cancer therapies have gained traction as an alternative to traditional treatment methods . Immunotherapy against cancer, in particular, is garnering attention for its ability to use the body’s immune cells to eradicate cancer cells. By activating dendritic cells (DCs) against cancer antigens, immunotherapy can elicit antigen-specific T cell immunity, which selectively kills cancer cells expressing the antigen .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent advancements in this field are noteworthy. 53 Specifically, nanomedicine-induced pyroptosis has attracted considerable attention as an efficacious approach to antitumor immunotherapy. 54 The purpose of this review is to provide a comprehensive and detailed account of the latest advancements in this emerging field (Table 1).…”
Section: Introductionmentioning
confidence: 99%